Dimethyloxalylglycine, a small molecule, synergistically increases the homing and angiogenic properties of human mesenchymal stromal cells when cultured as 3D spheroids. Issue 5 (8th February 2021) - Costa, Marta H. G.; Serra, Joana; McDevitt, Todd C.; Cabral, Joaquim M. S.; da Silva, Cláudia L.; Ferreira, Frederico Castelo
Abstract: Strategies aiming at increasing the survival and paracrine activity of human mesenchymal stromal cells (MSCs) are of utmost importance to achieve the full therapeutic potential of these cells. Herein, we propose both physical and biochemical strategies to enhance the survival, homing, angiogenic, and immunomodulatory properties of MSCs in vitro. To that purpose, we compared the effect of exposing either 2D monolayer or 3D spheroids of MSCs to (i) hypoxia (2% O2 ) or to (ii) a hypoxic‐mimetic small molecule, dimethyloxalylglycine (DMOG), with cells cultured at 21% O2 . 3D‐cultured MSC spheroids evidenced higher survival upon exposure to oxidative stress and expressed higher levels of factors involved in tissue repair processes, namely tumor necrosis factor‐stimulated gene‐6, matrix metalloproteinase‐2, and vascular endothelial growth factor. MSCs cultured as 3D spheroids and further exposed to hypoxia or hypoxic‐mimetic conditions provided by DMOG synergistically favored the expression of the cell surface marker C‐X‐C chemokine receptor type‐4, involved in homing processes to injured tissues, and adhesion to extracellular matrix components as fibronectin. These results highlight the role of ex vivo preconditioning approaches, presenting a novel strategy that combine biochemical stimuli with 3D spheroid organization of MSCs to maximize their tissue regeneration potential. Abstract : 3D‐cultured mesenchymal stromal cell (MSC) spheroids, exposed to hypoxia or hypoxia‐mimetic conditions provided by dimethyloxalylglycine, presented higher survival upon exposure to oxidative stress conditions and expressed higher levels of factors involved in tissue repair processes in comparison to their monolayer counterparts cultured under atmospheric levels of oxygen (21% O2 ). This work highlights the importance of developing preconditioning strategies that synergistically integrate 3D cell culture and biochemical stimuli to enhance the survival, homing, angiogenic, and immunomodulatory properties of MSCs in wound healing settings.